2017
DOI: 10.1088/1361-665x/aa6298
|View full text |Cite
|
Sign up to set email alerts
|

Direction-sensitive smart monitoring of structures using heterogeneous smartphone sensor data and coordinate system transformation

Abstract: Mobile, heterogeneous, and smart sensor networks produce pervasive structural health monitoring (SHM) information. With various embedded sensors, smartphones have emerged to innovate SHM by empowering citizens to serve as sensors. By default, smartphones meet the fundamental smart sensor criteria, thanks to the built-in processor, memory, wireless communication units and mobile operating system. SHM using smartphones, however, faces technical challenges due to citizen-induced uncertainties, undesired sensor-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…Previously, it has been shown that actual crowdsourcing results (results from uncontrolled citizens) matched well with the reference identification results [32]. These uncertainties are extensively studied in [48] including spatiotemporal variation of a citizen sensor [33], phone orientation which is subjected to change before, during, and after the measurements [34], and biomechanical distortions caused by human nature [50]. Therefore, in this paper, the main focus is on uncertainties induced by ground motions and FE model parameters.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, it has been shown that actual crowdsourcing results (results from uncontrolled citizens) matched well with the reference identification results [32]. These uncertainties are extensively studied in [48] including spatiotemporal variation of a citizen sensor [33], phone orientation which is subjected to change before, during, and after the measurements [34], and biomechanical distortions caused by human nature [50]. Therefore, in this paper, the main focus is on uncertainties induced by ground motions and FE model parameters.…”
Section: Methodsmentioning
confidence: 98%
“…The authors' previous works present the first vibration-based SHM system (CS4SHM) using crowdsourcing power [32] and offer multisensory solutions to citizen-induced errors by considering spatiotemporal [33] and directional [34] uncertainties. Without any prior engineering education and background, citizens as uncontrolled SHM device operators can provide a central server system with ubiquitous vibration data.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Likewise, in smartphone-based SHM systems, it is expected that the monitoring results are significantly affected by the uncontrollable sensing environment due to crowdsourcing initiatives. 27 These initiatives can result from pedestrian identity (height, weight, age, gender, etc.…”
Section: Biomechanical Modelsmentioning
confidence: 99%
“…26,27,31,32 Potential pedestrian postures and activities on a civil infrastructure are unlimited; therefore, only few common scenarios are tested in this study which include the following: smartphone (1) directly attached to the bridge deck surface, (2) resting in a bag on the deck, (3) in a pedestrian's pocket, and (4) in a backpack carried by a pedestrian. Table 1 summarizes the variation sources in structural vibration data extracted from pedestrians, sources of uncertainties, positive and negative extremes in sensing conditions.…”
Section: Field Testsmentioning
confidence: 99%
See 1 more Smart Citation